PENINGKATAN KESADARAN MASYARAKAT TERKAIT PELECEHAN SEKSUAL DALAM MEWUJUDKAN PARIWISATA RAMAH PEREMPUAN DI DESA LEMBANNA - Tamrin, Andi Febriana; Nurul Asrah (Merwinspy Publisher, 2024)
Lembanna Village is one of the villages located in Bulukumba district. According to a survey conducted by the Adventure Travel Trade Association (ATTA) in 2020, the tourism sector is dominated by female tourists compared to male tourists. Starting from solo-travelers to those in groups. However, the facilities and access offered in the tourism sector are still not friendly to the needs of women as tourists. This service activity aims to look at public awareness of sexual harassment and environmentally friendly tourism for women. This research uses a qualitative descriptive method. Data collection through interviews and using PAR (Participatory Action Research). The results show that the local government has not made security a top priority and there is still a lack of understanding of the local community on types of sexual harassment.